-3+4x=7-x

Simple and best practice solution for -3+4x=7-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+4x=7-x equation:


Simplifying
-3 + 4x = 7 + -1x

Solving
-3 + 4x = 7 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-3 + 4x + x = 7 + -1x + x

Combine like terms: 4x + x = 5x
-3 + 5x = 7 + -1x + x

Combine like terms: -1x + x = 0
-3 + 5x = 7 + 0
-3 + 5x = 7

Add '3' to each side of the equation.
-3 + 3 + 5x = 7 + 3

Combine like terms: -3 + 3 = 0
0 + 5x = 7 + 3
5x = 7 + 3

Combine like terms: 7 + 3 = 10
5x = 10

Divide each side by '5'.
x = 2

Simplifying
x = 2

See similar equations:

| 3(n-7)=2n-8 | | u^2+12u+36=0 | | 7+2x=-3+4x | | -3x+8=x-12 | | 2w^4x^4-32w^4= | | 2x+1/4+9/4 | | y=7x+37 | | 16u^2-u^2v^4= | | 2x-8(0)=24 | | 2(0)-8y=24 | | 0.2+6.51+2.03=a | | -8y=2 | | 3y=9x-24 | | -12.5+20.13=W | | x+x+0.56+x+0.56+1.08=10.51 | | c=9.8+(-2.5) | | 2x^2-3xy-5y^2=0 | | y=-12+(-9.6) | | y=1/4(0)-2 | | m/5+5=7/5 | | 2x-3xy-5y=0 | | y=1/4(4)-2 | | (11/12/44/5)-(11/12*44/5) | | 14.75+0.18=k | | 8-5x=4-6x | | 15/48=54 | | 8-1x=4-6x | | -6x^2+5y+6=0 | | 5y^2+34y+24=0 | | 3y^2+15y-18=0 | | 5x^2-7x+3=3x^2-2x | | x^2-14x+18=0 |

Equations solver categories